Mothers\' Awareness, regarding Orodental Health of their Children at age of 1-6 Years old - M. Naderifar; T. Akbarsharifi; H. Pairovi; H. Haghani (Iran University of Medical Sciences, 2006)
Background & Aim: Orodental health is one of the most important aspect of children's health. Care of mouth and teeth is important in children during childhood, because it guarantees the appropriate raising of permanent teeth. Therefore, mothers' awareness about orodental health is important, as a foundation for health promotion planning for children. The aim of this study, was to determine the knowledge of mothers about their childreans orodental health at age of 1-6 years old.   Material & Method: This was a cross-sectional study in which, questionnaires and interviews were used as tools for data gathering. Five hundred mothers of children at age of 1-6 years old, were selected by random sampling method that took part in the study.   Resulths: About 8.6% of mothers had low level knowledge, 44% had moderate knowledge and 47.4% had good knowledge regarding orodental health in children (P=0.000). The ANOVA test showed that significant correlation between the variables of knowledge and mothers' age as well as, mothers' education, children's age, economic situation of the families and residence area.   Conclusion: As mothers have great responsibilities about children's orodental health, therefore, increasing knowledge regarding this issue is important and planning educational programs for mothers would be necessary.